2015
DOI: 10.4149/bll_2015_066
|View full text |Cite
|
Sign up to set email alerts
|

Amount of folic acid in different types of nutrition used in the neonatal period

Abstract: BACKGROUND: Folic acid is one of the important supplements for adequate development during pregnancy. A higher intake of folic acid during pregnancy and lactation is recommended. METHODS: In prospective study the group of premature newborns (n = 52) and the type of nutrition were observed. The red blood cell (RBC) folate concentration levels were determined in the fi rst 24 hours after delivery, before and after oral treatment with folic acid (100 μg/day). Immunochemical analysis for the determination of folat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In the I. trimester, the most frequently used supplement was folic acid, which is important for adequate fetal development during the prenatal period. Its clear importance in pregnancy lies in the process of developing the brain and the nervous system, especially in the prevention of neural tube defects (22). In Slovakia, 5 per 10,000 live-born children are affected by congenital malformations of the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…In the I. trimester, the most frequently used supplement was folic acid, which is important for adequate fetal development during the prenatal period. Its clear importance in pregnancy lies in the process of developing the brain and the nervous system, especially in the prevention of neural tube defects (22). In Slovakia, 5 per 10,000 live-born children are affected by congenital malformations of the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Although in our circumstances, pregnant women do not typically suffer from a quantitative or qualitative vitamin deficiency, in the area of vitamin supplementation, it is essential to emphasize the beneficial impact of using FA. Numerous studies have demonstrated that this substance decreases the risk of NTDs by up to 72% (4,(103)(104)(105)116). Dietary supplementation with FA is recommended for all pregnant women in the amount of 0.4 mg per day (106) or 4 mg daily after a previously affected pregnancy (107).…”
Section: Vitamin Supplementationmentioning
confidence: 99%
“…By analysing the breast milk, we are able to optimize newborn enteral nutrition with fortifi ers. Apart from the macronutrients, fortifi ers contain other components such as folic acid (7). In addition to the determination of macronu-trients in human milk, clinical practice would benefi t also from the detection of micronutrients (trace elements and vitamins) in human milk.…”
Section: Introductionmentioning
confidence: 99%